Rediscovery of Endangered Tree Psydrax ficiformis, Lectotypication of Two Names and a New Combination in the Genus Psydrax (Rubiaceae) - Arigela, Ravi Kiran; Singh, R. Kr. (Indian Forester, 2020)
Psydrax ficiformis (Hook, f.) Bridson (Rubiaceae) is rediscovered after a century from Kodaikanal Wildlife Sanctuary, Tamil Nadu state, India. Detailed taxonomy and first photographs of the live plant are provided. A new combination is proposed for Canthium lanceolatum Arn. under the genus Psydrax Gaertn. and first time detailed taxonomic description is provided. Two names, Canthium ficiforme Hook. f. and C. lanceolatum Arn. are lectotypified here and images of the lectotype specimens are also given